Improving Digital Competency for Educators and Education Personnel Through Google Workspace for Education - Fauziah, Ai Samrotul; Nugroho, Fahmi Hasan (LP2M INSURI Ponorogo, 2024)
Fast-growing information technology impacts all aspects, including education, so all those involved in education must be able to use technology and information to facilitate work. This service aims to provide understanding, increase competence, and apply Google Workspace to education for educators and personnel. The method taken in this service is to use Community Based Research (CBR) or called Community Based Participatory Research (CBPR) is research based on a collaborative model between the community and the world of higher education that aims to carry out service learning actions to support social movements for the realization of social justice. The service method is carried out by holding workshops for partners. The implementation of the service begins by creating a website and school domain to create a Google Workspace for education and then conducting workshops on its use. The results of this service make MA Subulul Huda educators and education personnel competent in using Google Workspace for education.